Multi-omics analysis reveals genes and metabolites involved in Streptococcus suis biofilm formation - Haikun Wang; Qingying Fan; Yuxin Wang; Li Yi; Yang Wang (BMC Microbiology, 2024)
Abstract Background Streptococcus suis is an important zoonotic pathogen. Biofilm formation largely explains the difficulty in preventing and controlling S. suis. However, little is known about the molecular mechanism of S. suis biofilm formation. Results In this study, transcriptomic and metabolomic analyses of S. suis in biofilm and planktonic states were performed to identify key genes and metabolites involved in biofilm formation. A total of 789 differential genes and 365 differential metabolites were identified. By integrating transcriptomics and metabolomics, five main metabolic pathways were identified, including amino acid pathway, nucleotide metabolism pathway, carbon metabolism pathway, vitamin and cofactor metabolism pathway, and aminoacyl-tRNA biosynthesis metabolic pathway. Conclusions These results provide new insights for exploring the molecular mechanism of S. suis biofilm formation.